ANALISIS PENGARUH PEMOTONGAN TUNJANGAN KHUSUS PEMBINAAN KEUANGAN NEGARA (TKPKN) BAGI PEGAWAI YANG TIDAK HADIR PADA JAM KERJA DAN PERILAKU ANGGOTA ORGANISASI TERHADAP PENINGKATAN KEDISIPLINAN KERJA PEGAWAI DI KANTOR PENGAWASAN DAN PELAYANAN BEA DAN CUKAI K - Kurnia Eka Novianto, 08.3502.0556; Sutino, Sutino (Students Journal of Economic and Management, 2012)
Based on observations made at the Office of Surveillance and the Customs and Excise Service Associate Study Holy Excise, efforts to improve the discipline of employees in the Office of Surveillance and the Customs and Excise Service Associate Study Holy Excise has been done one way to cut the State Finance Development Special Benefit (TKPKN). Efforts to further disciplinary action of employees can be done through the behavior of members of an organization (Organization Citizenship Behavior). Behavior of members of an organization is very important, and is a business, actions and activities undertaken by the leadership to influence the employment is high. Thus it can be said that this approach would improve the behavior of members of theÂ organization and employee morale will make employees willing to work with management Key words: cutting benefits, improved behavior and discipline